Об устойчивости жидкой прослойки в композиции WC–Co–алмаз - Давиденко, С.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Using results of thermodynamic researches, some features of formation of structure of composite WC–Co–diamond are considered. The special attention is turned on occurrence of stability of liquid layers in these materials.